(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
The study examine the role of women in the anti-colonial movement, emphasizing the stories of those who emerged as potent agents of resistance by defying societal standards, gender norms, and colonial oppression. Kanaklata Barua of Assam is a powerful representation of young bravery and selflessness among these individuals. This study explores her role in the larger framework of women’s nationalist involvement, looking at how her acts subverted patriarchal norms in Assamese society as well as British authority. Narratives about male leaders have long dominated the history of India’s liberation struggle, obscuring the achievements of women, especially those who were less well-known and from the countryside (Sharma, 2010, p. 87). In order to give Kanaklata Barua and other female freedom warriors their proper place in the national narrative, the article will explore archival materials, regional histories, and existing scholarship on women’s engagement in the liberation movement. The analysis shows that their resistance was intricately linked to the mainstream nationalist movement rather than being on the periphery. The study emphasizes the need to incorporate women’s perspectives into India’s mainstream historiography through a critical reevaluation of historical narratives, so expanding our understanding of what national resistance entails.